An empirical-statistical model for laser cladding of Ti-6Al-4V powder on Ti-6Al-4V substrate. (1st March 2018) - Nabhani, Mohammad; Razavi, Reza Shoja; Barekat, Masoud
Highlights: Laser cladding of Ti-6Al-4V powder on Ti-6Al-4V substrate is investigated. The process parameters are related to the geometrical properties of single clad tracks. An empirical-statistical processing map is developed. Abstract: In this article, Ti-6Al-4V powder alloy was directly deposited on Ti-6Al-4V substrate using laser cladding process. In this process, some key parameters such as laser power ( P ), laser scanning rate ( V ) and powder feeding rate ( F ) play important roles. Using linear regression analysis, this paper develops the empirical-statistical relation between these key parameters and geometrical characteristics of single clad tracks (i.e. clad height, clad width, penetration depth, wetting angle, and dilution) as a combined parameter ( P α V β F γ ). The results indicated that the clad width linearly depended on PV −1/3 and powder feeding rate had no effect on it. The dilution controlled by a combined parameter as VF −1/2 and laser power was a dispensable factor. However, laser power was the dominant factor for the clad height, penetration depth, and wetting angle so that they were proportional to PV −1 F 1/4, PVF −1/8, and P 3/4 V −1 F −1/4, respectively. Based on the results of correlation coefficient ( R > 0 . 9) and analysis of residuals, it was confirmed that these empirical-statistical relations were in good agreement with the measured values of single clad tracks. Finally, these relations led to the design of a processing map that can predict the geometrical characteristics of the single clad tracks based on the key parameters.